An Application of Neural Network Solution in the Apparel Industry for Cutting Time Forecasting - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Artificial Neural Network is proposed to handle to estimating of marker making cutting time. Estimating the optimum cutting time greatly affects the production efficiency and daily production capacity of the cutting department. Using ANN system in a factory, different marking lengths and their obtained calculated cutting times, the data (from number of fabric layers, cutting blade speed, number of sizes, marking lengths, and cutting times) are applied to the system. Different fabric lays quantities end resulting cutting time actively possible fabric lays quantities for calculation the necessary cutting times estimated realized, the presentation of the most helpful optimum fabric lays quantities calculation for making decisions is made.
Keywords: Apparel Industry; calculating of fabric lays quantities; length of marker making; fabric cutting time; Artificial Neural Network; Levenberg-Marquardt algorithm